Mindfulness-based transformational learning for managing impulse buying - Renus Sermboonsang (2020)
© 2019, © 2019 Taylor & Francis Group, LLC. The authors focus on applying mindfulness-related concepts to business education by relying on transformational learning techniques for reducing impulse buying in a six-week Smart Consumer university class. A transformational learning program was designed including activities in the classroom as well as outside activities. They incorporated cognitive, affective, and conative aspects of student behaviors, aiming to effectively transform their impulse-buying behaviors. The initial test from the six-week pilot program shows changes in awareness and with some consumption behaviors toward less impulse buying. With a longer time frame in future programs, positive behavioral changes are likely to be more prominent. Implications abound for mindfulness-based transformational learning programs in business education that effect sustainable behaviors of students as our young generation members.